Apprehending the NAD+–ADPr-Dependent Systems in the Virus World - Lakshminarayan M. Iyer; A. Maxwell Burroughs; Vivek Anantharaman; L. Aravind (Viruses, 2022)
NAD+ and ADP-ribose (ADPr)-containing molecules are at the interface of virus–host conflicts across life encompassing RNA processing, restriction, lysogeny/dormancy and functional hijacking. We objectively defined the central components of the NAD+–ADPr networks involved in these conflicts and systematically surveyed 21,191 completely sequenced viral proteomes representative of all publicly available branches of the viral world to reconstruct a comprehensive picture of the viral NAD+–ADPr systems. These systems have been widely and repeatedly exploited by positive-strand RNA and DNA viruses, especially those with larger genomes and more intricate life-history strategies. We present evidence that ADP-ribosyltransferases (ARTs), ADPr-targeting Macro, NADAR and Nudix proteins are frequently packaged into virions, particularly in phages with contractile tails (Myoviruses), and deployed during infection to modify host macromolecules and counter NAD+-derived signals involved in viral restriction. Genes encoding NAD+–ADPr-utilizing domains were repeatedly exchanged between distantly related viruses, hosts and endo-parasites/symbionts, suggesting selection for them across the virus world. Contextual analysis indicates that the bacteriophage versions of ADPr-targeting domains are more likely to counter soluble ADPr derivatives, while the eukaryotic RNA viral versions might prefer macromolecular ADPr adducts. Finally, we also use comparative genomics to predict host systems involved in countering viral ADP ribosylation of host molecules.